1989
DOI: 10.1037/0021-9010.74.5.834
|View full text |Cite
|
Sign up to set email alerts
|

A realistic test of individual versus group consensus decision making.

Abstract: Nearly all research on the accuracy of individual versus group decision making has used ad hoc groups, artificial problems, and trivial or nonexistent reward contingencies. These studies have generally concluded that the knowledge base of the most competent group member appears to be the practical upper limit of group performance and that process gains will rarely be achieved. We studied individual versus group decision making by using data from 222 project teams, ranging in size from 3 to 8 members. These tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(178 citation statements)
references
References 31 publications
7
164
2
4
Order By: Relevance
“…6 Others have identified that team-based learning may benefit academically vulnerable students. [11][12][13][14][15] Student opinions of both courses were favorable. The main difference observed related to the usefulness of required readings and overall course coordination.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…6 Others have identified that team-based learning may benefit academically vulnerable students. [11][12][13][14][15] Student opinions of both courses were favorable. The main difference observed related to the usefulness of required readings and overall course coordination.…”
Section: Discussionmentioning
confidence: 89%
“…This is supported by research, which indicates that teams consistently outperform individuals. 13 Through the team-based learning process, team members learn from each other, which adds another dimension of learning. Team development and maturation is an important component of team-based and cooperative learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to both feminist and multicultural approaches to psychology, a diversity of viewpoints is valued, honored, and protected (Williams & Barber, 2004). In fact, the use of consensus has been shown to improve decision quality (Michaelsen, Watson, & Black, 1989;Sundstrom, Busby, & Bobrow, 1997) by taking into account both commonly held and minority views (Miller, 1989). Because subtle meanings may be conveyed through the interview process in CQR, this variety of viewpoints and experiences among the team members may help unravel the complexities and ambiguities of the data.…”
Section: The Consensus Processmentioning
confidence: 99%
“…Research by Michaelson, Watson and Black (1989) provides compelling evidence that collaboration and sharing outperform the efforts of the best non-sharing individual consistently. In this study, students took tests throughout a semester.…”
Section: To Share or Not To Share…mentioning
confidence: 99%